A validated LC‐MS/MS method for rapid determination of brazilin in rat plasma and its application to a pharmacokinetic study. (10th January 2013) - Deng, Zhipeng; Wang, Xin; Zhao, Huanxin; Cui, Shuxiang; Yao, Qingqiang; Bai, Hong
ABSTRACT: Brazilin is a major homoisoflavonoid component isolated from the dried heartwood of traditional Chinese medicine Caesalpinia sappan L., which is a natural red pigment used for histological staining. Herein a sensitive, specific and rapid analytical LC‐MS/MS method was established and validated for brazilin in rat plasma. After a simple step of protein precipitation using acetonitrile, plasma samples were analyzed using an LC‐MS/MS system. Brazilin and the IS (protosappanin B) were separated on a Diamonsil C18 analytical column (150 × 4.6 mm, 5 µm) using a mixture of water and 10 mm ammonium acetate in methanol (20:80, v/v) as mobile phase at a flow rate of 0.6 mL/min. The method was sensitive with a lower limit of quantitation of 10.0 ng/mL, with good linearity (r 2  ≥ 0.99) over the linear range 10.0–5000 ng/mL. All the validation data, such as accuracy and precision, matrix effect, extraction recovery and stability tests were within the required limits. The assay method was successfully applied to evaluate the pharmacokinetics parameters of brazilin after an oral dose of 100 mg/kg brazilin in rats. Copyright © 2013 John Wiley & Sons, Ltd.